Role of Rituximab as First Line Immunosuppressant in Primary Glomerulonephritis - Afzal, Aurangzeb; Khanum, Zohra; Ashraf, Sania; Liaqat, Myra; Mobushar, Jehangir Afzal; Arshed, Jawad; Saleem, Sidra; Bajwa, Beenish Abbas; Zafar, Adnan Ahmad; Shahzad, Anjum; Ahmed, Adeel (Indus Journal of Bioscience Research, 2025)
Background: Primary glomerulonephritis remains a significant cause of chronic kidney disease, often requiring immunosuppressive therapy. Rituximab, a monoclonal anti-CD20 antibody, has emerged as a potential first-line immunosuppressant. However, its efficacy across different histopathological subtypes remains unclear. This retrospective study evaluated the clinical and biochemical response to rituximab in patients with primary glomerulonephritis. Methods: This retrospective review analyzed medical records of patients treated with rituximab at the Nephrology Department of Lahore General Hospital from 2019 to 2023. A total of 18 patients with biopsy-proven primary glomerulonephritis who received rituximab as first-line immunosuppressive therapy were included. Patient data were retrieved, including baseline demographics, renal function tests, proteinuria, histopathological findings, and treatment response over six months. The primary outcomes were changes in serum creatinine, eGFR, and proteinuria at six months. Results: The study population included six patients with membranous nephropathy, four with FSGS, three with lupus nephritis, two with MPGN, and one each with MCD and IgA nephropathy. Proteinuria significantly decreased in patients with eGFR >30 mL/min/1.73m² (p<0.0001), while those with eGFR <30 mL/min/1.73m² showed no improvement (p=0.9). Histopathological response varied, with 35.7% of patients with mild fibrosis achieving complete remission, while none with moderate or severe fibrosis achieved full remission. Conclusion: Rituximab effectively reduces proteinuria in patients with preserved renal function, but its impact on eGFR remains limited. Histopathological severity correlates with treatment response, with poorer outcomes observed in patients with advanced fibrosis. Larger retrospective studies are needed to further evaluate rituximab’s role as a first-line therapy in primary glomerulonephritis.